OPTIMIZATION OF PHYSICAL CULTURE LESSONS IN PRIMARY SCHOOL ON THE BASE OF MOBILE GAMES’ APPLICATION - Shuba, L.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2017)
Purpose: to improve methodic of mobile games’ application for physical culture lessons’ optimization in primary school that would facilitate motor fitness increase. Material: in experiment 50 boys (7-9 yrs) from main health group (no health problems) participated. For training strength we chose games, which required short speed-power tensions with at moderate loads. The following objects were used: filled ball, dump bells, benches or partners. In games with overcoming own weight we used: wall bars, beams, vertical rope. Results: peculiar features of the improved methodic are as follows: for preparatory part we worked out ten separate complexes of general exercises in game form; for all parts of lesson mobile games were selected so that they should facilitate maximal development of physical qualities; each training was emotionally positively colored that motivate pupils’ wish to attend the lessons. Conclusions: for effective development of physical qualities the decisive factor was consideration of sensitive periods and complex approach to physical education lessons.